Interlinking of Indian rivers - Ghosh, A. K. (Asish Kumar), 1938-; Sikdar, P. K.; Dutta, Ashoke K. (Kolkata : ACB Publications, 2003)
Contributed articles.
Includes bibliographical references and index.
Keywords: River engineering -- India; Water resources development -- India; Rivers -- India